Selection of special vehicle for transportation of perishable freights by rail - T. I. Nabatchikova; S. N. Naumenko; A. V. Kostin; G. B. Gusev (Вестник Научно-исследовательского института железнодорожного транспорта)
Delivery of perishable freights in proper quality essentially depends on the correct choice of a special vehicle and the correct calculation of the delivery time. According to the requirements of the Rules for the transportation of perishable freights by rail, all special vehicles by January 1, 2022 must obtain certificates of compliance with the standards established by the Agreement on the International Transportation of Perishable Foodstuffs and on special vehicles intended for these transports. This requirement applies to special vehicles used both in international traffic and for transport of perishable freights within the country. The article presents a brief classification of special vehicles used for the transportation of perishable freights. Formulas are given that allow calculating duration of transportation of such freights and average temperature of the outside air along the entire route. Procedure for choosing a special vehicle for the already known duration of freight transportation has been developed. It is concluded that the procedure proposed by the authors allows choosing the optimal special vehicle for the transportation of perishable freights. Using this sequence of calculations makes it possible to take into account the maximum number of external factors that affect the duration of transportation.